Absence of Pathological Proof of Cancer Associated with Improved Outcomes in Early‐Stage Lung Cancer. Issue 7 (July 2016) - Shaikh, Talha; Churilla, Thomas M.; Murphy, Colin T.; Zaorsky, Nicholas G.; Haber, Alan; Hallman, Mark A.; Meyer, Joshua E.
ABSTRACT : Objectives: : The purpose of this study was to assess the trends in use of clinical diagnosis and its impact on treatment outcomes in patients receiving radiation therapy for early‐stage lung cancer. Methods: : The Surveillance, Epidemiology, and End Results registry was queried from 2004 to 2012 for patients at least 18 years old in whom stage I (clinical stage T1a–T2a) lung cancer had been diagnosed and who underwent radiation therapy alone. Trends in diagnostic confirmation patterns were characterized. A Cox proportional hazards model was used to assess overall survival, and competing risk regression analysis was used to assess cancer‐specific survival (CSS). Results: : A total of 7050 patients were included; the disease of 6399 of them (90.8%) was pathologically diagnosed and that of 651 (9.2%) was clinically diagnosed. There was no significant change in the utilization of clinical versus pathologic diagnosis ( p = 0.172) over time. Patients with T1 disease ( p < 0.001), tumors 0 to 1.9 cm in size ( p < 0.001), and upper lobe tumors ( p = 0.004) were more likely to have been clinically diagnosed. On multivariable analysis, clinical diagnosis was associated with an improved CSS (hazard ratio [HR] = 0.82, 95% confidence interval [CI]: 0.71–0.96) but was not associated with an improved overall survival (HR = 1.01, 95% CI: 0.90–1.13). When stratified by T stage, patients whose disease had been clinically diagnosed as stage T1a had an improved CSS (HR = 0.75, 95% CI: 0.58–0.96, p = 0.022). There was a trend toward improved CSS in patients with clinical stage T1b tumors (HR = 0.74, 95% CI: 0.55–1.00, p = 0.052). Conclusions: : The improved CSS in patients with a clinical diagnosis suggests treatment of benign disease, particularly in smaller tumors. Prudent patient selection is needed to reduce the potential for overtreatment.